Network Model of Revitalization in the Cittaslow Cities of the Warmińsko-Mazurskie Voivodship - Strzelecka, Elżbieta (Regional Barometer. Analyses & Prognoses, 2018)
The aim of this article is to present a network model of a revitalization of small towns unique in Poland and even in Europe . Fourteen small towns in the Warmińsko-Mazurskie Voivodship, thanks to their membership in the Cittaslow City network and the establishment of the Polish Cittaslow Association, received significant funds for their development under the Supralocal Revitalization Program of the Network of Cittaslow Cities for 2014–2020. This program is based on a hybrid model of urban development, which was created from the overlap of financial models (ERDF, ESF funds, own funds) and the so-called “social” revitalization model on developing in Poland Cittaslow model oriented to a good quality of life. This is an example of the efficient use by the network of cooperating cities of economies of scale in competing with other urban centers for development measures. Thanks to the unified diagnosis of existing problems in the physical, economic and social space of these cities (delimitation areas, delimitation indicators: unemployment rate and share of people using social assistance in the area revitalized in relation to the entire city), differentiated urban activities were undertaken in integrated financial projects that concerned the restriction of various social dysfunctions, including the problem of unemployment.